Adolescents Perceptions of Pro- and Antitobacco Imagery and Marketing: Qualitative Study of Students from Suva, Fiji. (25th August 2015) - Waqa, Gade; McCool, Judith; Snowdon, Wendy; Freeman, Becky
Abstract : Background . Many studies examining smoking uptake among young people in the Pacific have not included their exposure to tobacco control promotions in the media in their assessment. This study examines how Fijian students view tobacco and tobacco-related media depictions to gain insight into both drivers of smoking uptake and potential directions for prevention interventions. Methods . A sample of thirty Fijian students (15 male and 15 female) aged 14–17 years, was recruited from a Suva school between September and October 2013 and participated in a one-to-one in-depth interview about their views on tobacco use, media consumption patterns and preferences and awareness of tobacco use in media. Results . Despite radical developments in access to media, television remains the most popular. Yet, the majority of participants were unaware of any protobacco imagery on television or other entertainment media. Tobacco-related imagery was more likely to be seen in connection with point of sale advertising and branding. The advertising potential of the shop counter was acutely apparent to some participants and this space was considered highly influential. Conclusions . Despite the fact that the recently introduced graphic health warnings were generally well received, more can be done to extend the use of media for tobacco control benefits in Fiji.